Esophagogastric junction morphology assessment by high resolution manometry in obese patients candidate to bariatric surgery. (April 2016) - Tolone, Salvatore; Savarino, Edoardo; de Bortoli, Nicola; Frazzoni, Marzio; Furnari, Manuele; d'Alessandro, Antonio; Ruggiero, Roberto; Docimo, Giovanni; Brusciano, Luigi; Gili, Simona; Pirozzi, Raffaele; Parisi, Simona; et al.
Abstract: Introduction: Obesity is a strong independent risk factor of gastroesophageal reflux disease (GERD) symptoms and hiatal hernia development. Pure restrictive bariatric surgery should not be indicated in case of hiatal hernia and GERD. However it is unclear what is the real incidence of disruption of esophagogastric junction (EGJ) in patients candidate to bariatric surgery. Actually, high resolution manometry (HRM) can provide accurate information about EGJ morphology. Aim of this study was to describe the EGJ morphology determined by HRM in obese patients candidate to bariatric surgery and to verify if different EGJ morphologies are associated to GERD-related symptoms presence. Methods: All patients underwent a standardized questionnaire for symptom presence and severity, upper endoscopy, high resolution manometry (HRM). EGJ was classified as: Type I, no separation between the lower esophageal sphincter (LES) and crural diaphragm (CD); Type II, minimal separation (>1 and < 2 cm); Type III, >2 cm separation. Results: One hundred thirty-eight obese (BMI>35) subjects were studied. Ninety-eight obese patients referred at least one GERD-related symptom, whereas 40 subjects were symptom-free. According to HRM features, EGJ Type I morphology was documented in 51 (36.9%) patients, Type II in 48 (34.8%) and Type III in 39 (28.3%). EGJ Type III subjects were more frequently associated to Symptoms than EGJ Type I (38/39, 97.4%, vs. 21/59, 41.1% p < 0.001). Conclusions: Obese subjects candidate to bariatric surgery have a high risk of disruption of EGJ morphology. In particular, obese patients with hiatal hernia often refer pre-operative presence of GERD symptoms. Testing obese patients with HRM before undergoing bariatric surgery, especially for restrictive procedures, can be useful for assessing presence of hiatal hernia.